Legitimacy of Entrepreneurs in the Iron Triangle Concept. Which is Prioritized? Price, Quality or Service? - LARASDIPUTRA, Gde Deny; KAWISANA, Putu Gede Wisnu Permana; YOGIARTA, I Made (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to understand how entrepreneurs, especially members of the Indonesian Young Entrepreneurs Association (HIPMI) Denpasar branch, prioritize and balance price, quality, and service factors in running their businesses. Using an interpretive approach and in-depth interview method, this study explores entrepreneurs' experiences and strategies in applying the Iron Triangle Concept to face market competition. The research findings show that the priority of one factor is influenced by market conditions, consumer needs, and the business's position in the growth cycle. Entrepreneurs who prioritize price tend to use competitive strategies to attract consumers, while those who prioritize quality focus on improving the reputation of products or services. On the other hand, superior service is an important factor in building long-term customer loyalty.This study confirms that business success lies in the ability to balance these three factors adaptively according to market dynamics. In addition, these findings provide practical insights for novice entrepreneurs in understanding how to manage the basic elements that are important for building business sustainability and legitimacy. This study contributes to the entrepreneurship literature by offering strategic guidance based on real experiences for entrepreneurs in managing the complexity of competitive markets.